STUDI KASUS : FIBROSARCOMA PADA ANJING POMERANIAN MIX - Simarmata, Yohanes T. R. M. R.; Biru, Desi M. A.; Restiati, Ni Made (JURNAL KAJIAN VETERINER, 2021)
Fibrosarcoma is a malignant neoplasm of fibroblast that commonly found in middle-aged or older dogs. Breed and sex do not influence the incidence of fibrosarcoma. A 10 years old grey female mix Pomeranian with a bodyweight of 9.2 kg showed a semi-solid mass, with meat-like consistency that felt integrated with the tissue underneath. A mass with a diameter of ± 5 cm had been found in the left thigh near the anus. The other two unusual masses with smaller size (diameter ±1 cm) were also found at lateral sinister near extremities cranial of the body. A serial of diagnostic check-ups, such as physical and clinical check-up, USG, haematology, cytology, and histopathology tests was run to examine the dog condition. The USG result showed hypoechoic masses with slightly anechoic appearances. The haematology analysis showed a decrease in lymphocyte, MCV and hematocrit, meanwhile the granulocyte, MCHC and MHC showed an increasing trend. The cytology test revealed a fat-like vacuolization. Furthermore, the histology examination indicating the presence of large hyperchromic oval cells. The histopathology examination also found fibroblast cells that suspected as tumour cells with mitotic and infiltrated oval cores. Thus, the dog was diagnosed with fibrosarcoma and the prognosis was dubious. The surgery was done to remove the tumour masses.